Implementation e-government initiatives among Malaysian local authorities - Abu Bakar, Ahmad Bakeri; Junurham, Nur Leyni Nilam Putri (2013)
This paper was to study the implementation of the eGovernment initiatives among the local authorities in Malaysia which are under the jurisdiction of the local governments by using the Web Presence Measurement Model. The findings showed that the City council came out top in terms of achievement for the five Stages of Web Presence while the District council came out last which means a good number of indicators are absent from the District council websites/portals The findings also showed that the local authorities operating in the State of Selangor were much more advanced in term of representation for their websites/portals compared to those found in the State of Sabah which is located at the bottom of the list. Lessons from this study indicate that local authorities operating in constituencies with high income per capita such as Selangor are able to integrate more facilities in their websites. However, social network facilities such as Facebook and Twitter are being provided by all the local authorities websites. It is expected that the evaluation of the local authorities websites will provide a clear indication as to the extent of e-government implementation among local authorities in Malaysia.